Dissecting causal relationships between gut microbiota, blood metabolites, and glioblastoma multiforme: a two-sample Mendelian randomization study - Chen, Xuan; Han, Lihui; Xu, Wenzhe (Frontiers in Microbiology, 2024)
Background Given the increasing interest in the role of gut microbiota in glioblastoma multiforme (GBM), our objective was to examine the potential causal relationship between gut microbiota and GBM, as well as the mediating effects of specific metabolites. Methods A bidirectional two-sample Mendelian randomization (MR) analysis was conducted to investigate the associations between 196 microbial taxa and GBM. A two-step MR technique was used to identify significant mediators in this relationship. Subsequently, a mediation analysis was performed to explore and quantify the mediating effects of specific metabolites on the causal relationship between gut microbiota and GBM. Results Five taxa showed significant associations with GBM. Among them, family Victivallaceae [odds ratio (OR): 1.95; 95% confidence interval (CI): 1.21, 3.13; P=0.005] and genus Lactococcus (OR: 1.81; 95% CI: 1.04, 3.15; P=0.036) were positively correlated with the risk of GBM, while phylum Cyanobacteria had a protective effect against GBM (OR: 0.45; 95% CI: 0.22, 0.89; P=0.021). The mediation analysis revealed that the connections among family Victivallaceae, genus Lactococcus, phylum Cyanobacteria and GBM were mediated by Methyl-4-hydroxybenzoate sulfate, phosphoethanolamine and dehydroepiandrosterone sulfate. Each of these accounted for 7.27%, 7.98% and 8.65%, respectively. Conclusions Our study provides evidence supporting a potential causal association between certain gut microbiota taxa and GBM. The study highlights the central role of gut microbiota in GBM pathogenesis and their interactions with vital serum metabolites. This paves the way for potential novel therapeutic interventions in GBM management.